FORMULATION, CHARACTERIZATION, AND IN VITRO EVALUATION OF NOVEL MICROEMULSION-BASED SPRAY FOR TOPICAL DELIVERY OF ISOTRETINOIN - Wani, Ashwini; Sanghani, Chintan; Wani, Swapnil (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The present study aimed at the development of a suitable formulation for the treatment of acne using microemulsion-based topical spray system. In this study, we have designed and evaluated novel isotretinoin microemulsion-based spray and gel using basil oil. The rationale of work is to develop single topical formulation with multiple effects by combining effect of retinoid (prevention of comedones formation) and natural oil like basil oil (antibacterial, anti-inflammatory, and penetration enhancer). Methods: The optimized microemulsion-based spray comprised basil oil, Kolliphor RH40, Ethanol, and water was prepared by an aqueous titration method with the help of a ternary phase diagram. The microemulsion-based gel was prepared using Carbopol ETD 2020. The formulations were evaluated for their physicochemical properties. The formulations were subjected to antibacterial activity against Propionibacterium acnes, Staphylococcus epidermidis, and Staphylococcus aureus using cup plate method against hydrogen peroxide as standard. Finally, the drug released from spray and gel formulations was studied and compared to a commercially available product. Results: Isotretinoin microemulsion-spray showed highest flux (27.67Â±0.12 Î¼g/cm2/h) in comparison to formulated microemulsion gel (21.81Â±0.103 Î¼g/cm2/h) and conventional marketed gel (19.29Â±0.34 Î¼g/cm2/h). The particle size of optimized microemulsion was found to be 68.43 nm. The results indicate that the formulated microemulsion-based spray presents a promising alternative for acne therapy. Conclusion: This mentioned delivery system presented several benefits such as photostability, better patient compliance, antibacterial activity, and good penetration into the desired skin layer when compared to in vitro diffusion of conventional gel and microemulsion-based gel. Â